2006
DOI: 10.1158/1541-7786.mcr-06-0050
|View full text |Cite
|
Sign up to set email alerts
|

An Autocrine Loop Involving Ret and Glial Cell–Derived Neurotrophic Factor Mediates Retinoic Acid–Induced Neuroblastoma Cell Differentiation

Abstract: In several neuroblastoma cell lines,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…It is well known that upon ATRA treatment BE(2)C cells show a decrease in the proliferation rate and neurite outgrowth [Bierau et al, 2002;Lee and Kim, 2004;Cerchia et al, 2006]. We observed that MF exposure significantly potentiated the effects of ATRA treatment.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is well known that upon ATRA treatment BE(2)C cells show a decrease in the proliferation rate and neurite outgrowth [Bierau et al, 2002;Lee and Kim, 2004;Cerchia et al, 2006]. We observed that MF exposure significantly potentiated the effects of ATRA treatment.…”
Section: Discussionsupporting
confidence: 52%
“…BE(2)C cell line is mainly composed of undifferentiated neuroblast-like cells, and can slightly differentiate toward a neuronal phenotype upon all-trans-retinoic acid (ATRA) treatment [Bierau et al, 2002;Lee and Kim, 2004;Cerchia et al, 2006;Jeong et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have concluded that RET plays a major role in differentiation and proliferation (21,51). It participates in a reciprocal loop between stromal mesenchyme and the ureteric bud epithelium; vitamin Adependent signals secreted by stromal cells control Ret expression in the ureteric bud.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of TLR2, a specific polymorphism (R753N) has been linked to increased susceptibility to tuberculosis (39). Interestingly, a different mutation associated with TLR2, upstream of the coding region, affects the development of asthma (40). Only children from farmers with this mutation show a reduced prevalence of asthma, linking TLR2 to the protective effects seen in rural populations vs urban populations (41).…”
Section: Tlr-mediated Signalingmentioning
confidence: 99%